Pectus Excavatum and Pectus Carinatum in dogs - Souza, Claudia Luvian; Baia, Giovanna Oliveira; Rezende, Bianca Costa; Jaworski, Lorena Tavares de Brito Nery; Prass, Daniela; Néspoli, Pedro Eduardo Brandini; de Almeida, Arleana do Bom Parto Ferreira; Sousa, Valéria Régia Franco (Acta Scientiae Veterinariae, 2020)
Background: Deformities of the anterior thoracic wall are called pectus: pectus excavatum and pectus carinatum. Pectus excavatum is characterised by dorsal deviation of the caudal region of the sternum while pectus carinatum consists of protrusion of the sternum and/or adjacent cartilage. Both defects may remain symptom-free, but respiratory and cardiac abnormalities have been reported. Another deformity observed in dogs is the swimming dog syndrome, which consists of the lateral opening of the thoracic and pelvic limbs, associated with the pedalling movement. These disorders are frequently reported in medical practice, are considered rare among canines. This report aims to describe a case of pectus excavatum associated with the swimming dog syndrome (Case 1) and another case of pectus carinatum (Case 2). Case: In Case 1, an approximately 45-day-old male American Pitbull canine had difficulty standing. Physical examination revealed hyperextension of the thoracic and pelvic limb joints and flattening of the thorax. After radiographic examination, pectus excavatum and the swimming dog syndrome were confirmed. The conservative treatment with splinting and hydrotherapy was chosen. At the 3-month follow-up, slight improvement in the limbs and irregular and unsatisfactory growth of the thorax leading to episodes of dyspnoea were observed. In Case 2, a female Pug, approximately 2 months old, had a thorax deformity. Physical examination revealed thorax protrusion, confirmed on radiography as pectus carinatum. Conservative therapy was provided using compressive bandage. One month later, the tutor reported improvement in the condition and absence of respiratory changes. Discussion: Pectus deformities has low incidence, and cases to pectus carinatum, there is a sexual predisposition, that is, males are more predisposed, differing from Case 2, a female dog. In the cases of pectus excavatum, no genetic alteration was directly related to its occurrence, although familial occurrence is reported in humans, as in Case 1, in which the patient was the only one of this litter to present this deformity. Though the possibility is lower, the acquired aetiology has been described in other cases. In pectus carinatum, there is the possibility of an acquired aetiology, which corroborates Case 2, considering that the canine had no history of inbreeding, nor family history. However, it is important consider racial predisposition, where there is an increasing number of cases of pectus carinatum in brachycephalic canines. Respiratory symptoms are frequently reported in cases of pectus excavatum, which the evolution of the condition occurred in Case 1, that can be explained by the displacement of organs or the restriction to ventilation. Humans have shown that pectus excavatum reduces static lung function. Case 2 showed no clinical signs, despite this presented dextrocardia, which in the future may confer cardiac dysfunctions. The diagnosis for pectus is considered simple. Performed only by radiography, it can be complemented by echocardiography. In both cases, conservative treatment was the choice. However, in Case 1 there was no success due to the degree of patient involvement, unlike Case 2, which had a better development of the thoracic wall, ensuring better quality of life for the patient. Thus, it is possible to conclude that some differences were found in these two reported cases when compared to others described in the literature. The radiographic diagnosis is confirmatory, and the therapy must be adequate to the degree of thoracic wall deformity. In addition, the prognosis is more reserved for pectus excavatum than pectus carinatum.